2007
DOI: 10.1016/j.febslet.2007.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of the extra‐ and intracellular domains of the yeast cell wall integrity sensors Mid2 and Wsc1

Abstract: Cell wall integrity signalling in Saccharomyces cerevisiae provides a model for the regulation of fungal wall biosynthesis. Chimers of the major plasma membrane sensors Wsc1 and Mid2 fused to GFP have been employed to show that intracellular and membrane distribution is only dependent on a membrane-anchored cytoplasmic tail. Phenotypic analyses of chimeric sensors in an isogenic Dmid2 Dwsc1 double deletion strain indicate that this tail, provided that it is linked to an extracellular domain, also determines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 27 publications
7
68
1
Order By: Relevance
“…Early studies confirmed their plasma membrane localization and suggested that Wsc1-GFP localizes to sites of cell wall remodelling [7,39,55]. This was confirmed by studies showing the accumulation of Wsc1-GFP in growing buds and, later on, at the bud neck during cytokinesis, with a constant redistribution of the sensor between the plasma membrane and internal compartments [51]. In contrast, Mid2 forms a patchy, largely immobile network throughout the plasma membrane in vegetatively growing yeast cells.…”
Section: Sensor Distribution and Dynamicssupporting
confidence: 53%
See 3 more Smart Citations
“…Early studies confirmed their plasma membrane localization and suggested that Wsc1-GFP localizes to sites of cell wall remodelling [7,39,55]. This was confirmed by studies showing the accumulation of Wsc1-GFP in growing buds and, later on, at the bud neck during cytokinesis, with a constant redistribution of the sensor between the plasma membrane and internal compartments [51]. In contrast, Mid2 forms a patchy, largely immobile network throughout the plasma membrane in vegetatively growing yeast cells.…”
Section: Sensor Distribution and Dynamicssupporting
confidence: 53%
“…It was proposed that Wsc1 would act primarily during vegetative growth, whereas Mid2 would be more involved in the mating response, with some functional overlap [42]. This hypothesis was substantiated by the observed sensor distributions described above, with Wsc1-GFP dynamically localizing to sites of cell wall construction and Mid2-GFP moving into the shmoo-tip during mating [19,51]. Further hints for the structural basis of sensor specificity and dynamics were obtained from studies of chimeric proteins and the comparison to the homologous sensors from K. lactis.…”
Section: Sensor Distribution and Dynamicssupporting
confidence: 49%
See 2 more Smart Citations
“…A similar example of microcompartmentation within the yeast plasma membrane is the punctuated and sometimes polarized distribution of the CWI (for c ell w all i ntegrity) sensors (Straede and Heinisch , 2007 ). In brief, the CWI-m itogen a ctivated p rotein k inase (MAPK) signaling pathway is triggered by stress at the yeast cell surface (either at the cell wall or at the plasma membrane), which is recognized by a five-membered family of transmembrane sensors (namely, Wsc1 to Wsc3, Mid2, Mtl1; Figure 2 ) (reviewed in Jendretzki et al , 2011 ).…”
Section: Compartmentation Of Cell Wall Integrity Sensorsmentioning
confidence: 99%